2019
DOI: 10.1038/s12276-019-0350-z
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids sustain pancreatic cancer growth by regulating lipid metabolism

Abstract: Branched-chain amino acid (BCAA) catabolism and high levels of enzymes in the BCAA metabolic pathway have recently been shown to be associated with cancer growth and survival. However, the precise roles of BCAA metabolism in cancer growth and survival remain largely unclear. Here, we found that BCAA metabolism has an important role in human pancreatic ductal adenocarcinoma (PDAC) growth by regulating lipogenesis. Compared with nontransformed human pancreatic ductal (HPDE) cells, PDAC cells exhibited significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 40 publications
2
80
0
Order By: Relevance
“…Knockdown of the E1α subunit of the BCKDH complex (BCKDHA) substantially inhibits PDAC cell proliferation in vitro and in mice [ 9 ]. Although BCKDHA knockdown has no significant impact on the levels of TCA cycle intermediates or oxygen consumption rate, but significantly impedes fatty acid synthesis in PDAC cells [ 9 ]. Whether or not BCAAs are used as the carbon source for the biosynthesis of fatty acids in PDAC remains to be investigated.…”
Section: The Mechanisms Of Altered Bcaa Metabolism-mediated Cancer Prmentioning
confidence: 99%
“…Knockdown of the E1α subunit of the BCKDH complex (BCKDHA) substantially inhibits PDAC cell proliferation in vitro and in mice [ 9 ]. Although BCKDHA knockdown has no significant impact on the levels of TCA cycle intermediates or oxygen consumption rate, but significantly impedes fatty acid synthesis in PDAC cells [ 9 ]. Whether or not BCAAs are used as the carbon source for the biosynthesis of fatty acids in PDAC remains to be investigated.…”
Section: The Mechanisms Of Altered Bcaa Metabolism-mediated Cancer Prmentioning
confidence: 99%
“… 16–18 Recently, Lee et al observed that branched-chain amino acids sustain metabolism and thus play a main role in pancreatic ductal adenocarcinoma (PDAC) growth by adjusting lipogenesis. 19 HSDL2 has received widespread attention for its possible involvement in lipid metabolism, and it is also well known as one of the major tumor markers when lipid metabolism is abnormal. However, the expression of HSDL2 in cell growth and lipid metabolism of PC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide evidence for dependency on the BCKDH complex and suggest its synergistic involvement with BCAT2 in regulating BCAA metabolism in PDAC cells. Recent studies investigated BCAT2’s role in PDAC development and found BCAT2 is elevated in PDAC models 42 , 43 . Our work develops further understanding of BCAA metabolism in the PDAC TME, especially in context of the pancreatic cancer-cell centric observations of previous studies.…”
Section: Discussionmentioning
confidence: 99%